„Uczta” Arystotelesa – analiza wybranych świadectw i fragmentów dialogu Stagiryty - Głodowska, Anna (Collectanea Philologica, 2019)
Among the works of Aristotle there are also dialogues, a literary genre, represented in ancient Greek literature above all by Plato. Although Aristotelian dialogues were not preserved to our times, on the basis of mentions found in the works of other ancient authors, an image of form and content of Aristotle’s dialogues may be drawn. The article aims to analyze selected testimonies and fragments concerning Aristotle’s Symposium, and to discuss motives and topics which appear in the dialogue of Plato’s pupil.